Maternal protein restriction during pregnancy and lactation affects the development of muscle fibers and neuromuscular junctions in rats. Issue 1 (23rd September 2016) - Confortim, Heloisa Deola; Jerônimo, Leslie Cazetta; Centenaro, Lígia Aline; Pinheiro, Patrícia Fernanda Felipe; Matheus, Selma Maria Michelin; Torrejais, Marcia Miranda
ABSTRACT: Introduction : A balanced maternal diet is a determining factor in normal fetal development. The objective of this study was to evaluate the effects of maternal protein restriction during pregnancy and lactation on muscle fiber and neuromuscular junction (NMJ) morphology of rat offspring at 21 days of age. Methods : Wistar rats were divided into a control group (CG), offspring of mothers fed a normal protein diet (17%), and a restricted group (RG), offspring of mothers fed a low‐protein diet (6%). After a period of lactation, the animals were euthanized, and soleus muscles were obtained from pups for analysis. Results : The soleus muscles of the RG exhibited an increase of 133% in the number of fibers and of 79% in the amount of nuclei. Moreover, the number of NMJs was lower in the restricted group than in the CG. Conclusions : Maternal protein restriction alters the normal development of the neuromuscular system. Muscle Nerve 55 : 109–115, 2017